FROM PERSONAL NARRATIVE TO SOCIAL CHANGE: REIMAGINING ABILITY IN MALINI CHIB’S ONE LITTLE FINGER - Varun Gulati (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper offers a multidimensional reading of Malini Chib’s memoir One Little Finger, situating it at the intersection of disability studies, literary analysis, and Indic philosophical thought. Drawing on frameworks from Rosemarie Garland-Thomson, Lennard J. Davis, and Martha C. Nussbaum, the study examines how Chib’s narrative challenges entrenched hierarchies of ability and redefines notions of “normalcy.” Philosophical parallels with Ekatva (the unity of existence) in the Upanishads and the inclusivist ethos of the Bhagavad Gita inform a reading of the memoir as an exploration of interconnectedness, resilience, and shared responsibility. The discussion foregrounds Chib’s reflections on education, mobility, and relational bonds, treating them as sites where personal agency converges with collective goodwill to create possibilities for social change. Literary allusions, from Shakespeare’s calls for empathy to the subversion of fatalism in Julius Caesar, amplify the memoir’s cultural depth. By rejecting binaries such as inclusion versus exclusion, Chib reframes challenges as opportunities for creative adaptation, illustrating how lived experience can inspire structural rethinking. Ultimately, One Little Finger emerges as both a personal chronicle of growth and a philosophical invitation to reimagine the social fabric, where equity, dignity, and mutual flourishing are central to the human experience.